Morphometric and morphologic analysis of the foramen spinosum in the Slovenian population with clinical correlations - Šink, Žiga; Umek, Nejc; Cvetko, Erika (PeerJ, 2023)
Background The foramen spinosum (FS) is a pivotal passage for neurovascular structures within the skull base. We performed a detailed morphometric and morphological analysis of the FS to emphasize its clinical relevance. Materials & Methods The study was performed on dried skull specimens obtained from the anatomical collections of the Institute of Anatomy and Institute of Forensic Medicine of the University of Ljubljana. The morphometric and morphologic features of FS in 126 whole human skulls and 15 skull halves were analyzed, including dimensions, shape, and other anatomical variations, as well as relationships to surrounding structures. Measurements were done with a digital sliding caliper. Results The mean length and width of the FS were 2.45 ± 0.65 mm and 2.03 ± 0.53 mm on the right side and 2.49 ± 0.61 mm and 2.08 ± 0.48 mm on the left side. The most frequently observed shape was round (56.7%), followed by oval (28.2%), irregular (8.7%) and drop shaped (6.3%). Several anatomical variations were also noted, including FS duplication, confluences with other foramina, and FS obstruction due to marginal bony outgrowths. Conclusion The FS exhibits notable interindividual differences in anatomical characteristics which should be considered during neurosurgical procedures and radiological interventions in the skull base.
Keywords: Foramen spinosum; Sphenoid spine; Morphometry; Anatomical variations; Middle meningeal artery; Zygomatic root